A Preliminary Exploration of the Relationships Between Student-Created OER, Sustainability, and Students' Success - Wiley, David; Webb, Ashley; Weston, Sarah; Tonks, DeLaina (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2017)
This article explores the relationship between open educational resources (OER) created by students for use by other students, the long-term sustainability of the movement toward OER, and the success of students who use OER created by other students as part of their core curricular materials. We begin by providing definitions and a broader context for thinking about the possibility of student-created OER. We then describe a course context in which student-created OER have been slowly integrated into an online class over several years and examine the impact on student learning associated with their introduction.